Turkish Voter Response to Government Incompetence and Corruption Related to the 1999 Earthquakes - Ali T. Akarca; Aysit Tansel (Turkish Economic Association, 2012)
The two major earthquakes which struck northwestern Turkey in 1999, caused enormous amounts of death and destruction, and exposed rampant government corruption involving construction and zoning code violations, as a factor magnifying the disaster. The opposition parties and one of the incumbent parties which participated in previous national governments and held power in current and past municipal administrations were responsible for that. The other two incumbent parties came to power only a short time before the earthquakes and controlled almost none of the local administrations in the disaster zone. They on the other hand, were responsible for the incompetence shown in providing relief, for involvement in corruption related to those efforts, and for failing to prosecute the businessmen who constructed the shoddy buildings and the corrupt officials who permitted them. How voters responded to these in the 2002 parliamentary elections is investigated, using cross-provincial data, controlling for other social, political and economic factors. The fact that different groups of parties were responsible for different types of corruption and mismanagement provided us with a unique data to differentiate between voter responses to corruption and incompetence, and to corruption which has occurred before and after the earthquakes. Our results show that voters punished all of the political parties which participated in governments during the previous decade. The party in charge of the ministry responsible for disaster relief, and parties that controlled more of the city administrations in the quake zone were blamed more. The newly formed Justice and Development Party (AKP) was the main beneficiary of the votes lost by these parties. Our results corroborate the view in the corruption literature that voters react drastically only when the corruption is massive, the information on it highly-credible and well-publicized, involves large number of political parties, not accompanied by competent governance, and a non-corrupt alternative is available.
Keywords: D72; D73; H84; 330; Turkey; Natural disaster; Earthquake; Corruption; Government performance; Elections; Voter behavior; Party preference; Erdbeben; Humanitäre Hilfe; Korruption; Wahlverhalten; Türkei